Transparent Logics. Small Differences with Huge Consequences - Kosterec, Miloš, (New Research in the History of Western Philosophy ;, 2024)
The book presents Transparent Intensional Logic in several of its latest realisations in such a way that it makes a case for the system and demonstrates how the theory can be applied to a wide range of cases. The work strikes a good balance betw